Designed Omnidirectional Antenna of Quarter-Mode Substrate-Integrated Waveguide Element with Characteristic Mode Analysis - Wei Hu; Liangfu Peng; Tao Tang; Maged A. Aldhaeebi; Thamer S. Almoneef; Jaouhar Mouine (Micromachines)
This study investigates the design of omnidirectional antennas, using a characteristic mode analysis (CMA), and explores two distinct feeding methods. The first method employs equal-amplitude and in-phase excitation across all ports, whereas the second method utilizes equal-amplitude excitation with a 180° phase difference between adjacent ports. Both designs achieve operating bandwidths of 2.45–2.58 GHz and 2.42–2.45 GHz, respectively, with peak gains of 4.1 dBi and 4.4 dBi at 2.45 GHz. The proposed antennas exhibited high gain and low-profile characteristics, making them well-suited for applications in wireless energy harvesting.